Impact of Input Use on Biomass Attributes and Carbon Mitigation in Agroforestry Systems of Indian Himalaya - Goswam, Sandhya; Verma, K. S.; Pala, Nazir A. (Indian Forester, 2016)
In the present study, the authors investigated the effect of input use for biomass attributes and carbon mitigation in agroforestry. The study was carried out in Kwalkhad watershed Himachal Pradesh, India and falls in the transitional zone between the Shiwalik or outer Himalayas and middle Himalayas. The watershed is covered by the survey of India topographical map 53F/I (1:50,000). The annual crop sequences and the functional components used under each sequence were taken as the criterion to classify the different system units as: low input, medium input or high input use system units. Annual crop sequences cereals + pulses + vegetables fallow (CPV-F), cereals + pulses fallow (CP-F) were taken as low input use; cereals + pulses + vegetables cereals + vegetables (CPV-CV), cereals + pulses - cereals + vegetables (CP-CV) as medium input use; and cereals + vegetables cereals + vegetables (CV-CV), cereals + vegetables - vegetables (CV-V), vegetables - vegetables (V-V) were taken as high input use sequences. In all the systems maximum accumulated as well as retained biomass was recorded under the high input use systems with CV-CV annual crop sequence. The values ranged from 229.78 to 459.81 q/ha and 104.14 to 179.10 q/ha, respectively for accumulated and retained biomass. However, for biomass removal no particular relationship was obtained with input levels. The carbon mitigation varied across different system units and was of the order: AHS (7.15 Mg ha-1) > ASH (7.03 Mg ha-1) > AS (4.69 Mg ha-1) > AH (3.55 Mg ha-1). Input use levels affected biomass attributes and hence, carbon sequestration and emission of different agroforestry systems also varied.